Analysis of the Level of Community Adaptation to Flood Disasters in Pesawahan Village, Porong District, Sidoarjo Regency - Syahfira Ray; Sabino Mariano; Hamdan Maulana Arsyad (CV Bumi Spasial, 2026)
Pesawahan Village experiences annual flooding that results in significant property losses and economic disruption, however, these impacts do not diminish the residents determination to remain and survive within these disaster-prone landscapes. The drivers of these disasters are inextricably linked to heightened vulnerability intensified by the anthropogenic impact of Lapindo mud waste on local river systems and the strategic adaptations communities implement to remain within these high-risk areas. This research focuses on analyzing the level of adaptation of the community in dealing with the vulnerability of the disaster. The study utilized a representative sample of 89 families, calculated with a 90% confidence level and a 10% margin of error, reflecting the exploratory and localized nature of this community-based research. Primary data were elicited through questionnaires and semi structured interviews, complemented by systematic field observations. The observation protocol specifically targeted visual markers of physical adaptation, including the elevation of residential structures, the reinforcement of village road infrastructure, and the status of environmental drainage systems. The data analysis technique was carried out using interval and percentage scales. The level of community adaptation to flood disasters as a whole is relatively high, supported by the success of the community in making significant physical and social adaptations. Operationalizing John W. Bennett’s Ecological Transition Theory through 28 diagnostic indicators, the study found a highly homogeneous adaptive response: 88 of the 89 respondents were classified within the high adaptation level, with only one individual categorized at a medium level.High adaptation is evidenced by improving village roads, raising house buildings, and mutual cooperation to clean the surrounding environment.